Hubungan Motivasi dengan Tingkat Kepatuhan Perawat dalam Melaksanakan Handover di Ruang Rawat Inap - oktavia via (Jurnal Medika Hutama, 2021)
Handover is a method or technique which is used to convey information about patients from the nurse who was on guard earlier to the nurse who will be on guard next. Incorrect handover implementation can endanger patient safety. This esearch aims to determine the relationship of motivation with nurse compliance in implementing handover in the inpatient room at Regional Hospital of Petala Bumi, Riau Province. This research used quantitative with a descriptive design and with cross-sectional approach. The research instrument used were questionnaires observation sheets. The sample of this research was 40 respondents who worked in the inpatient room at Regional Hospital of Petala Bumi, Riau Province by using total sampling techniques. The analysis used was a univariate analysis with a frequency distribution table and bivariate analysis using fisher’s test. The result showed that motivation was not related with nurse compliance in implementing handover in the inpatient room with Pvalue =0,407 (P≤ 0,05). From the result this reseach are expected to Regional Hospital of Petala Bumi, Riau Province in order to conduct a seminar or training about handover to improve nurse compliance in implementing handover. Bibliography : 45 (2006-2018) Keywords :Handover, Motivation, the level of nurse compliance